Faktor-Faktor Penentu Customer Delight Sate Ayam Ponorogo di Rumah Makan Kota Ponorogo dan Surabaya - Fahrasyahda, Marsha Amanda; Nurhadi, Eko; Wahyuning Laily, Dona (JURNAL AGRICA, 2025)
Indonesia as a country with a large area and a variety of islands, and tribes make culinary in Indonesia very diverse. Ponorogo Chicken Satay Culinary is one of the diversity of satay in Indonesia, this satay is a culinary that is characteristic of the city of Ponorogo. The purpose of this study is to determine what factors determine the existence of customer delight in Ponorogo Chicken Satay consumers at Ponorogo and Surabaya Restaurants. The population of this study were all consumers who had purchased Ponorogo Chicken Satay at each restaurant. Determination of the sample using non-probability sampling, namely purposive sampling with the condition that consumers have bought at least twice and are at least 17 years old. The analysis method used is Factor Analysis. The main factor causing Customer Delight at RM Sate Ayam Ponorogo in Ponorogo is Finishing Touch with a variance percentage value of 39.939%. While at RM Sate Ayam Ponorogo in Surabaya is Justice with a variance percentage value of 43.896%.